Nonparametric M-Estimation with Long-Memory Errors - Jan Beran; Sucharita Gosh; Philipp Sibbertsen (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
We investigate the behavior of nonparametric kernel M-estimators in the presence of long-memory errors. The optimal bandwidth and a central limit theorem are obtained. It turns out that in the Gaussian case all kernel M-estimators have the same limiting normal distribution. The motivation behind this study is illustrated with an example.
urn:nbn:de:bsz:352-opus-5199
Keywords: 330; Zeitreihenanalyse; Nichtparametrisches Verfahren; Theorie; Statistischer Fehler